The history pages of orthodox pilgrimage: from worship to pilgrim tourism - TIMOFEEVA, L.S.; AKHMETOVA, A.R.; GALIMZYANOVA, L.R.; FOMINYKH, A.D.; MUNINA, Y.V. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The article deals with the history of the pilgrimage development in pre-revolutionary and post-Soviet Russia. The content of the concepts "pilgrimage" and "religious tourism" in modern literature is under definition. The article considers specifically the motivation of religious tourists and the possibility of their church going through pilgrimage. The article also analyzes travels made by pilgrims, both with the support of religious organizations and travel companies, taking into account modern legal and economic requirements, for which this type of tourism is regarded as a type of business activity with the possible participation of religious associations. RESUMEN El artículo aborda la historia del desarrollo de la peregrinación en la Rusia pre-revolucionaria y post soviética. El contenido de los conceptos "peregrinación" y "turismo religioso" en la literatura moderna está bajo definición. El artículo considera específicamente la motivación de los turistas religiosos y la posibilidad de que su iglesia pase por la peregrinación. Analiza también, los viajes realizados por los peregrinos tanto con el apoyo de organizaciones religiosas como con el de las compañías de viajes, teniendo en cuenta los requisitos legales y económicos modernos, por lo que este tipo de turismo se considera como un tipo de actividad empresarial.